Evaluating In-house vs. Outsourced Electronic Development in the Automotive Industry - Andersson,Svante; Lejon,William (2025)
Background: As electronic control units (ECUs) become increasingly complex and central to vehicle functionality, Original Equipment Manufacturers (OEMs) face strategic decisions on whether to develop such components in-house or outsource them. These make-or-buy decisions affect not only cost but also innovation potential, lead times, and organizational capability. Purpose: To evaluate the implications of different levels of supply chain integration in ECU development and provide Scania with insights to guide future development strategies. Research Questions: (1) What levels of supply chain integration are theoretically possible? (2) What are the advantages and disadvantages of the different levels of supply chain integration? (3) What levels of supply chain integration are practically implementable at a leading commercial vehicle manufacturer’s ECU development? (4) How do the different levels of supply chain integration in the development and production of electronics perform? Methodology: The study combines a literature review with an embedded single-case study of two internal development groups at Scania. Data was collected through semi-structured interviews, internal documentation, and a quantitative simulation of the development of an actual Scania ECU. Findings: Higher integration levels can reduce development lead times, improve coordination, and strengthen internal capabilities, but require greater organizational investment and alignment. Co-development models may offer a strategic middle ground between efficiency and control. Key words: Supply Chain Integration, Make-or-Buy, Electronic Control Units, Resource-Based View, Transaction Cost Economics, Automotive Industry
Keywords: Supply Chain Integration; Make-or-Buy; Electronic Control Units; Resource-Based View; Transaction Cost Economics; Automotive Industry